2017
DOI: 10.1186/s13075-017-1446-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe intestinal dysbiosis is prevalent in primary Sjögren’s syndrome and is associated with systemic disease activity

Abstract: BackgroundAltered microbial composition of the intestine, commonly referred to as dysbiosis, has been associated with several autoimmune diseases including primary Sjögren’s syndrome (pSS). The aims of the current study were to study the intestinal microbial balance in pSS and to identify clinical features associated with dysbiosis.MethodsForty-two consecutive pSS patients and 35 age-matched and sex-matched control subjects were included in the study in an open clinic setting. Stool samples were analyzed for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 40 publications
2
93
0
4
Order By: Relevance
“…In our study, gut dysbiosis were only noted in Sjögren's syndrome while patients with environmental dry eye syndrome maintained similar gut microbiota compositions with those of healthy volunteers. Although, studies for gut microbiota in Sjögren's syndrome have not been conducted much so far, this dysbiosis can be supported by previous studies [20,21]. One study reported that gut dysbiosis was prevalent in Sjögren's syndrome and was associated with systemic severity, but they did not mention how the composition of the gut microbiota changed [21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study, gut dysbiosis were only noted in Sjögren's syndrome while patients with environmental dry eye syndrome maintained similar gut microbiota compositions with those of healthy volunteers. Although, studies for gut microbiota in Sjögren's syndrome have not been conducted much so far, this dysbiosis can be supported by previous studies [20,21]. One study reported that gut dysbiosis was prevalent in Sjögren's syndrome and was associated with systemic severity, but they did not mention how the composition of the gut microbiota changed [21].…”
Section: Discussionmentioning
confidence: 94%
“…Dysbiotic gut microbiome is also reported to be associated with ocular mucosal diseases in SS [20]. However, there are only few reports regarding the dysbiosis of the gut in Sjögren's syndrome [20,21]. Given that food habits and ethnicity may affect the gut microbiota, investigation of the gut microbiota of SS patients should be further conducted in different regions including Asia.…”
Section: Introductionmentioning
confidence: 99%
“…A study comparing patients with SS ( n = 39) and SLE ( n = 30) to population controls ( n = 965) found that faecal microbiota in both patient cohorts was characterized by lower bacterial richness and lower Firmicutes/Bacteroidetes ratios compared to controls . In another study, stool samples from 42 patients with SS and 35 age‐ and sex‐matched controls were analysed for dysbiosis using a 16s rRNA–microbiota test . Severe dysbiosis was significantly more prevalent in patients with SS than in controls (21% vs. 3%), and the patients with severe dysbiosis had higher ESSDAI scores, lower C4, and higher levels of faecal calprotectin.…”
Section: Biological Factorsmentioning
confidence: 99%
“…Gastrointestinal involvement in pSS 130 may lead to esophageal dysfunction, 131,132 gastroparesis, 133 gastroesophageal reflux, 134 atrophic gastritis, enteropathy, 135 pancreatic insufficiency, 136 hepatic involvement (including autoimmune hepatitis and fibrosis), [136][137][138] pseudolymphoma of the liver, 139 and dysbiosis (alteration of gut microbial flora). [140][141][142] SS may occur in combination with other autoimmune disorders such as PBC. 143 In a retrospective study of 125 patients with PBC, 77 (61.6%) had PBC only and 48 (38.4%) had both PBC and SS.…”
Section: Gastrointestinal Involvementmentioning
confidence: 99%